Creativity and meaning: including meaning as a component of creative solutions. Issue 4 (5th October 2018) - Sääksjärvi, Maria; Gonçalves, Milene
Abstract: The goal of this paper is to examine meaning as a component of creativity. We take a demand-based approach for conceptualizing meaning, and propose that it emerges from user needs instead of emerging from already existing creative solutions. Meaning is proposed as a third component of creativity, alongside novelty and usefulness. We test this proposition in a pre-study, and two empirical studies. In the pre-study, designers define creativity and provide examples of solutions that they deem creative. The results of the pre-study yield a 24-item scale for assessing creativity. Then, we conduct two empirical studies, in which we utilize the created scale for measuring creativity, and for examining the components arising thereof. In the first study, we ask creators (design engineering students) to generate ideas for one of two design briefs. Afterwards, creators were asked to rate their own creations, on the 24-item creativity scale. Here, we find a four-factor solution for creative outcomes, consisting of the dimensions novelty, usefulness, cleverness, and meaning. In the second study, we ask independent evaluators (individuals with related and relevant degrees) to assess the creators' work on the creativity scale. Here, we find a three-factor solution for creative outcomes, consisting of the dimensions novelty, usefulness, and meaning. In both studies, meaning emerged as a separate component of creativity. Additionally, in both studies, it accounted for variance that was unaccounted for by novelty and usefulness, thereby increasing the overall explanatory power of creative solutions. These findings strongly speak of meaning as a third component of creativity.